Design and development of self-balancing climbing machine for oil palm harvesting - Shokripour, Hamed (2010)
Oil palm is a major plantation crop in Malaysia. The country successfully developed the oil palm plantation industry during the past three decades and it is now one of the largest palm oil producers in the world. However, due to the lack of specific machinery for harvesting oil palm fruits, the harvesting operation is still done using the traditional method of a sharp knife that is attached to the head of a long pole. This traditional method of harvesting requires strong workers with special experience and skills. In the face of a decreasing number of these skilled workers, their salaries have increased, which has added to the cost of harvesting. Furthermore, using the traditional method, workers cannot harvest fruits from trees which are too tall. The project was to design, fabricate and test a new self-balancing and remote-controlled four wheeled climbing robot for oil palm trees and a special cutting system for cleaning the fronds. A control system was designed and fabricated for the climbing robot to keep the robot’s balance during the climbing process by individually controlling the speed of each wheel. A dual axis tilt sensor was used to simultaneously measure the angle of tilt for both X and Y axes. In addition, a carrier machine was designed and fabricated to bear different equipment – such as the cutting system, digital camera and sprayer – and carry these around the tree trunk to enable them to undertake different processes. The operator controls the climbing robot and carrier machine via a specific remote control. The speeds of the DC motors are controlled by a Pulse-width modulation (PWM). A specific program was written with Bascome software in Basic language for an ATmega64 microcontroller as the Arithmetic and Logic Unit of the robot. All parts of the robot were successfully tested in laboratory and field conditions. The time and motion study was carried out on several trees. The average time required to place the robot around the tree, then have it climb up, cut a frond, and descend, was about eight (8) minutes for each tree. The maximum angle of tilt around X and Y axes were eight (8) and six (6) degrees respectively. The robot successfully negotiated the irregularities of the tree trunk’s surface and automatically set its size relative to changes in the diameter of the tree trunk. The carrier machine carried the cutting machine and moved smoothly around the tree trunk. Both the climbing robot and carrier machine responded successfully to the commands sent from the remote control by the operator.